Aerosol particle measurements at three stationary sites in the megacity of Paris during summer 2009: meteorology and air mass origin dominate aerosol particle composition and size distribution - F. Freutel; J. Schneider; F. Drewnick; S.-L. von der Weiden-Reinmüller; M. Crippa; A. S. H. Prévôt; U. Baltensperger; L. Poulain; A. Wiedensohler; J. Sciare; R. Sarda-Estève; J. F. Burkhart; et al. (Atmospheric Chemistry and Physics, 2013)
During July 2009, a one-month measurement campaign was performed in the megacity of Paris. Amongst other measurement platforms, three stationary sites distributed over an area of 40 km in diameter in the greater Paris region enabled a detailed characterization of the aerosol particle and gas phase. Simulation results from the FLEXPART dispersion model were used to distinguish between different types of air masses sampled. It was found that the origin of air masses had a large influence on measured mass concentrations of the secondary species particulate sulphate, nitrate, ammonium, and oxygenated organic aerosol measured with the Aerodyne aerosol mass spectrometer in the submicron particle size range: particularly high concentrations of these species (about 4 μg m−3, 2 μg m−3, 2 μg m−3, and 7 μg m−3, respectively) were measured when aged material was advected from continental Europe, while for air masses originating from the Atlantic, much lower mass concentrations of these species were observed (about 1 μg m−3, 0.2 μg m−3, 0.4 μg m−3, and 1–3 μg m−3, respectively). For the primary emission tracers hydrocarbon-like organic aerosol, black carbon, and NOx it was found that apart from diurnal source strength variations and proximity to emission sources, local meteorology had the largest influence on measured concentrations, with higher wind speeds leading to larger dilution and therefore smaller measured concentrations. Also the shape of particle size distributions was affected by wind speed and air mass origin. Quasi-Lagrangian measurements performed under connected flow conditions between the three stationary sites were used to estimate the influence of the Paris emission plume onto its surroundings, which was found to be rather small. Rough estimates for the impact of the Paris emission plume on the suburban areas can be inferred from these measurements: Volume mixing ratios of 1–14 ppb of NOx, and upper limits for mass concentrations of about 1.5 μg m−3 of black carbon and of about 3 μg m−3 of hydrocarbon-like organic aerosol can be deduced which originate from both, local emissions and the overall Paris emission plume. The secondary aerosol particle phase species were found to be not significantly influenced by the Paris megacity, indicating their regional origin. The submicron aerosol mass concentrations of particulate sulphate, nitrate, and ammonium measured during time periods when air masses were advected from eastern central Europe were found to be similar to what has been found from other measurement campaigns in Paris and south-central France for this type of air mass origin, indicating that the results presented here are also more generally valid.